Numerical study on the axial segregation dynamics of a binary-size granular mixture in a three-dimensional rotating drum - Yang, Shiliang (2018)
Granular materials are ubiquitous in our daily life and inherent in multitudinous industrial processes. Differences in the granular properties such as size and density inevitably induce segregation. By means of the discrete element method, a binary-size mixture in a three-dimensional rotating drum is numerically simulated to explore the segregation dynamics of the granular material along the axial direction. Snapshots of the distribution of the two particle types in the rotating drum are presented with respect to time to illustrate the spatial evolution of the size-induced segregation structure. The space-time plots of various axial characteristics indicate that (i) radial segregation does not affect the axial distribution of total mass and mass fraction, but axial segregation leads to the formation of axial bands; (ii) greater non-dimensionalized collision forces for both the large and small particles develop where the large particles dominate; and (iii) axial segregation gives rise to the variation of the gyration radii of both particle types along the drum length. In addition, axial flow of both particle types in both directions indicates the dynamic axial exchanges, and the effect of the end walls on the axial flow direction is limited to less than 25% of the drum length from the end walls.